ANALYSIS OF ELECTRIC CIGARETTE USE BEHAVIOR IN YOUTH AGED 15-24 YEARS IN THE SURABAYA CITY - Dwi Handayani; Vivi Iftitah Illaeni; Pulih Asih, Akas Yekti; Ibad, Mursyidul (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2023)
The results of the GATS survey show an increase in the prevalence of electronic smokers up to 10 times, from 0.3% in 2011 to 3% in 2021. East Java Province is one of the provinces with a percentage of electric smokers over the age of 15, as much as 27.28%. This study aimed to analyze the behavior of using e-cigarettes in adolescents aged 15-24 years in Surabaya city. This research method is the quantitative descriptive-analytic cross-sectional approach. The sample of this research is adolescents aged 15-24 years in Surabaya city, with a total of 157 respondents. This research uses an accidental sampling technique. Data analysis is in the form of univariate and bivariate analysis (chi-square). The results showed that the respondents' intention to use e-cigarettes was mostly in the weak category, 59.2%. Support from friends in using e-cigarettes is mostly in the strong category, 61.1%. Family support for using e-cigarettes is mostly in the weak category, 55.8%. Most respondents are in the difficult category of accessing health information related to the dangers of e-cigarettes, which is 62.4%. Access to the affordability of most respondents in the easy category is 65.6%. The conclusions in this study are that there is a strong relationship between the intention and behavior of using e-cigarettes in adolescents, there is a low relationship between friend support, family support, access to health information related to the dangers of using e-cigarettes, access to convenience and behavior of using e-cigarettes in adolescents. It is hoped that healthcare profetionals can provide preventive efforts to educate the public, especially adolescents, regarding the dangers of e-cigarettes for health to prevent chronic diseases caused by e-cigarettes.